The Mediating Role of Dark Personality Traits in Explaining the Structural Relationships Between the Desire to Control Others and Women's Sense of Happiness - Mahdavi, Mahdi; Mehrinejad, Seyed Abolghasem; Karami, Abolfazl; Roshan Chesli, Rasoul (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of the current study was to investigate the mediating role of dark personality traits in explaining the structural relationships between the desire to control others and women's sense of happiness.Methods: The research method was descriptive correlational with a structural equation modeling approach. The population of the study comprised all married women in Tehran in the year 2021. The sample size was 448 participants, selected through purposive convenience sampling and assessed using the Taghizadeh and Shadmehri Happiness Scale (2016), the Graham-Kwan and Archer Controlling Behaviors Scale (2005), and the Johnson and Webster Dark Personality Traits Scale (2010). Data analysis was performed using structural equation modeling.Findings: The analysis indicated that the structural model of the study fits well with the collected data, and dark personality traits significantly and negatively mediate the relationship between the desire to control others and women's sense of happiness.Conclusion: Thus, it can be stated that the higher the desire to control others and the presence of dark personality traits, the lower the sense of happiness, which can be a useful insight in couples' counseling.